Wind optimization of flight profiles through the Reykjavik control area - Ninna Björg Ólafsdóttir 1988- (2014)
Fuel efficiency has become an increasingly important factor in the aviation industry. The main reason is that fuel is the largest part of airlines operating expenses. Furthermore there has been increased awareness of the impact of man-made climate changes. The adoption of new aircraft fleets that are more fuel efficient can take decades. Operational improvements are however an effective way of improving fuel efficiency and environmental performance in the near term. Increasing fuel efficiency by optimizing aircraft tracks is an example of an operational improvement technique. In this study an optimization algorithm that finds the shortest path in terms of time of flight for aircraft in the cruise phase was designed and implemented. The algorithm finds the most fuel efficient routes by taking advantage of accurate knowledge of wind direction and wind speed. The focus was on flights within the Reykjavik Air Traffic Control Area, where the effects of the North Atlantic jet stream were relatively strong. The results showed promising potential for improvements in lateral trajectory optimization where all the flights optimized showed some potential for fuel burn and thereby emissions to be reduced. Furthermore, the lateral trajectories were optimized 1,000 feet above and below the actual flight level. The results showed that there is a significant change in fuel consumption per minute between cruising altitudes, where the fuel consumption decreases with increased altitude. Therefore,although the highest cruising altitude resulted most often in the highest traveling time, the total fuel burn was always the lowest when the highest altitude was chosen. As the aviation industry is a large scale industry only a small rate of fuel burn reduction, like the one achieved in this study, can add up to substantial amount of fuel burn reduction and thereby CO2 emission savings. This research project was supported in part by a grant from Isavia. Isavia